HUBUNGAN BERAT BAYI LAHIR DENGAN PERTUMBUHAN PADA BATITA DI PRAKTIK MANDIRI BIDAN NURVITA SARI DESA SIMPANG CAMPANG OKU SELATAN TAHUN 2020 - Ririn Anggraini; Pini Milenia Yupita; Su’aidy A. Rahman; Raty Rusmiana (Jurnal Kesehatan Abdurrahman, 2021)
Basic growth that takes place from toddler to preschool will affect the development and growth of the child then. LBW babies can affect growth because since the womb, they have experienced intrauterine growth retardation. The purpose of this study was to determine the relationship between birth weight and growth in toddlers at PMB Nurvita Sari, South OKU Simpang Campang Village in 2020. This study used a cross sectional research design. The researcher used total sampling to take a sample. The results obtained from 50 respondents who were born normally as many as 42 respondents (84%), and LBW by 8 respondents (16%). And of the 50 baby respondents who experienced normal growth as many as 34 respondents (68%) and not normal as many as 16 respondents (32%). The results of the study on the relationship between birth weight and body weight / height (BB/TB) showed a p value of 0.900> 0.05, it means that there was no significant relationship between birth weight and body weight / height (BB/TB). The relationship between birth weight and height / age (TB/U) showed a p value of 0.079> 0.05, meaning that there was no significant relationship between birth weight and height for age (height / age). And the relationship between birth weight and growth shows a p value of 0.716> 0.05, which means that there was no significant relationship between birth weight and growth in toddlers. So the conclusion of this study is there was no relationship between birth weight and growth in toddlers. In this study, the secondary data did not contain head circumference data, so it is hoped that the health workers at PMB Nurvita Sari will better understand the importance of the head circumference indicator, so that growth monitoring in children can be monitored effectively.